Pengaruh Gaya Kepemimpinan Transaksional & Transformasional Terhadap Prestasi Kerja Melalui Kedisiplinan Kerja Pada Kantor Pemerintahan Desa Dengkol Kec. Singosari Kab. Malang Jawa Timur - Windy Meilinda Auerin; Abdul Kodir Djaelani; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbtractThis study aims to determine and analyze the effect of transactional leadership style on work performance through work discipline, the effect of transformational leadership style on work performance through work discipline. This research is a type of explanatory research, with a quantitative approach. The analytical method used is path analysis. The sample used in this study were all employees of the dengkol village government office, totaling 73 employees.The results of this study indicate that transactional and transformational leadership styles have a significant effect on work discipline, leadership styles have no significant effect on work performance, transformational leadership styles have a significant effect on work performance, work discipline has a significant effect on work performance, work discipline mediates the relationship between transactional leadership styles with work performance, discipline does not mediate the relationship between transformational leadership style and job performance. Keywords: transactional leadership style, transformational, work discipline and work performance